Novel Polymeric Hybrid Nanocarrier for Curcumin and Survivin shRNA Co-delivery Augments Tumor Penetration and Promotes Synergistic Tumor Suppression - Xu, Bei; Zhou, Wen; Cheng, Lizhi; Zhou, Yang; Fang, Aiping; Jin, Chaohui; Zeng, Jun; Song, Xiangrong; Guo, Xia (Frontiers in Chemistry, 2020)
The major barrier for coadministration of gene medicine with small molecular chemotherapeutic drug is the inadequate tumor penetration and transfection in solid tumors. In this study, a novel polymeric nanocarrier with integrated properties of tumor penetration, nuclear targeting, and pH-responsive features was designed, and further used to achieve synergistic anti-tumor effect of curcumin (CUR) and survivin shRNA (pSUR). The polymeric hybrid nanocarrier was constructed from the FDA approved polymer PLGA and a novel conjugated triblock polymer W5R4K-PEG2K-PHIS (WPH). CUR and pSUR were simultaneously encapsulated in the dual-drug-loaded nanoparticles (CUR/pSUR-NPs) by a modified double-emulsion solvent evaporation (W/O/W) method. The obtained nanoparticles exhibited better pharmaceutical properties with a uniform spherical morphology and sustained release manners of CUR and pSUR. Excellent features including preferable cellular uptake, efficient endosomal escape, enhanced tumor penetration and elevated transfection efficiency were further proved. Additionally, a markedly enhanced antitumor efficacy of CUR/shRNA-NPs was achieved on SKOV-3 and Hela cells. The synergistic antitumor effect involved the inhibition of tumor cell proliferation, induction of cell apoptosis and activation of caspase-3 pathways. This work sets up an innovative co-delivery nanosystem to suppress tumor growth, contributing to the development of a comprehensive nanoparticulate strategy for future clinical applications.